Analisis Faktor-Faktor yang Mempengaruhi Return on Asset pada KB Bukopin Syariah dengan Pendekatan Error Correction Model - Shinta Pramudya Wardani; Rendra Erdkhadifa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Sharia bank operations are oriented towards obtaining as much profit as possible. Banks that obtain maximum profits indicate better bank management performance. However, a bank that fails to generate optimal profits can become an urgency in itself and result in bank bankruptcy. The condition of low bank profits experienced by KB Bukopin Syariah, which in recent years has experienced decline in profitability (ROA) reaching negative numbers. In order to prevent this bad profit condition, a study is needed to analyze the factors that have an influence ROA which hinder banks in earning profits. Several factors are thought to influence ROA, namely CAR, BOPO, NPF, and FDR. The approach used in this research is quantitative associative type and purposive sampling as a technique for collecting data. The data in this research is secondary data obtained by documenting the quarterly annual report of KB Bukopin Syariah for the period 2009-2023. The method applied is the error correction model (ECM) which shows long and short term effects and is assisted by EViews software. The test results showed that the CAR and FDR variables had a positive and insignificant effect in both the long and short term on ROA of KB Bukopin Syariah. Meanwhile, the BOPO and NPF variables have a significant negative effect on the ROA of KB Bukopin Syariah in the long and short term